Variations in milk, udder skin, and fecal microbiota and their relationships with blood metabolites and milk composition in dairy cows - AoDaohu; Karin, Akada; Kiiru, Gathinji Peter; Naoki, Nishino (Letters in applied microbiology, 2024)
This study examined the milk, udder skin, feces, and bedding microbiota in a dairy farm. Blood metabolites concentration and milk composition were also determined to examine their relationship with variations in the microbiota. Samples were collected from 10 healthy cows during the summers of 2018 and 2020. Milk protein, fat, and solid-not-fat contents were higher, and blood urea nitrogen and nonesterified fatty acid levels were lower in the 2020 samples. Principal coordinate analysis demonstrated that milk, udder skin, and fecal microbiota were separate groups. Year-to-year differences were distinct for milk and udder skin microbiota; however, the fecal microbiota of the 2018 and 2020 samples were similar. The bedding microbiota grouped with the udder skin microbiota of the 2018 samples. Although nonpathogens found as prevalent taxa in udder skin microbiota were likely to be found as abundant taxa in milk microbiota, selection and elimination occurred during transmission. Network analysis suggested that bacterial taxa of milk, udder skin, and fecal microbiota were unrelated to blood metabolites and milk composition, regardless of pathogens or nonpathogens.